2018
DOI: 10.1002/2211-5463.12547
|View full text |Cite
|
Sign up to set email alerts
|

Human amnion‐derived mesenchymal stem cells promote osteogenesis of human bone marrow mesenchymal stem cells against glucolipotoxicity

Abstract: Epidemiological evidence suggests that diabetes mellitus ( DM ) is an important factor in promoting periodontitis. It not only affects the attachment of connective tissue but also causes loss of alveolar bone. Hence, there is an urgent need to find an effective treatment for DM ‐induced bone deficiency. This study aimed to investigate the effects of human amniotic mesenchymal stem cells ( HAMSC s) on the proliferation and osteogenic different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Compared with human adipose stem cells, hAMSCs possessed more chondroprotective by improving OA chondrocyte viability, increasing cartilage glycosaminoglycan content and reducing OA synovial macrophage M1:M2 ratio [ 186 ]. hAMSCs also attenuated diabetes-induced dysfunction of bone marrow mesenchymal stem cells (BM-MSCs) through promoting p38 mitogen-activated protein kinase and VEGF-mediated antioxidant activity [ 187 ]. Studies showed that hAMSCs promoted implant osseointegration and bone regeneration by accelerating mineralized deposition rates on implant surfaces and in bone-augmented areas [ 188 ] and enhanced new bone formation by inducing M2 macrophages to secrete BMP-2 and VEGF in rabbits’ skull defects [ 189 ].…”
Section: Cell-based Therapy With Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…Compared with human adipose stem cells, hAMSCs possessed more chondroprotective by improving OA chondrocyte viability, increasing cartilage glycosaminoglycan content and reducing OA synovial macrophage M1:M2 ratio [ 186 ]. hAMSCs also attenuated diabetes-induced dysfunction of bone marrow mesenchymal stem cells (BM-MSCs) through promoting p38 mitogen-activated protein kinase and VEGF-mediated antioxidant activity [ 187 ]. Studies showed that hAMSCs promoted implant osseointegration and bone regeneration by accelerating mineralized deposition rates on implant surfaces and in bone-augmented areas [ 188 ] and enhanced new bone formation by inducing M2 macrophages to secrete BMP-2 and VEGF in rabbits’ skull defects [ 189 ].…”
Section: Cell-based Therapy With Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…Their transplantation therapy has been applied in a variety of animal models and clinical studies. [5][6][7] Recent studies have shown that BMSCs have a therapeutic effect not mainly relying on the characteristics of stem cells, but rather relying on their paracrine and endocrine effects at the transplantation sites, affecting the microenvironment of the body, exerting immunoregulatory functions, and promoting the nutritional regeneration of damaged tissues. [8][9][10] Among them, exosomes dominate the paracrine role of BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Both cell populations showed comparable proliferation rates as shown by PDT assay ( Figure 1 ), which is consistent with other reports [ 24 , 25 , 34 , 37 ]. In contrast, BM-MSCs cultured under high glucose (HG) [ 38 ] or other diabetes simulation conditions such as a combination of HG and palmitic acid [ 39 ] or advanced glycated endproducts (AGEs) [ 40 ] showed significantly lower proliferation capacities. Such studies usually use nonphysiological high concentrations of glucose [ 41 ] and may not fully replicate the T2DM microenvironment that entails hyperglycaemia as well as high levels of AGEs, reactive oxygen species (ROS), hyperlipidaemia, hyperinsulinemia and inflammatory cytokines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are also in contrast with the findings of Ying et al [ 59 ], who cultured BM-MSCs under osteogenic and HG osteogenic conditions and found that HG cultures caused ALPL downregulation. Healthy BM-MSCs cultured under HG [ 59 ], HG and palmitic acid [ 39 ] and T2DM serum [ 60 ] showed lower expression of both RUNX2 and OCN compared to control cultures. Nonetheless, these diabetes simulation cultures have some limitations, as mentioned above.…”
Section: Discussionmentioning
confidence: 99%